Synthesis and characterization of two new aryl cyclobutyl ketoethyl methacrylate monomers and their polymers - Erol, I; Ilter, Z; Coskun, M; Ahmedzade, M (John Wiley & Sons Inc, 2001)
Two new methacrylate monomers, 2-[3-(6-tetralino)-3-methylcyclobutyl]-2-ketoethyl methacrylate (TKEMA) and 2-(3-mesityl-3-methylcyclobutyl)-2-ketoethyl methacrylate (MKEMA), were obtained from the reaction of 1-chloroacetyl-3-methyl-3-arylcyclobutane with sodium methacrylate. The oxime and hydrazone derivatives of poly(TKEMA) and poly(MKEMA) were prepared with hydroxylamine and 2,4-dinitrophenyl hydrazine. Poly(TKEMA) and poly(MKEMA), their oxime and hydrazone derivatives, and the monomers were characterized with Fourier transform infrared and NMR techniques. The glass-transition temperatures and thermal stability of the polymers and their oxime and hydrazone derivatives were compared. (C) 2001 John Wiley & Sons Inc.
Keywords: ketoethylmethacrylate; hydrazone and oksime derivatives; thermal stability